2022
DOI: 10.3390/foods11101436
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae I4 Showed Alleviating Effects on Dextran Sulfate Sodium-Induced Colitis of Balb/c Mice

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel disease. The purpose of this study was to investigate the ameliorating effects of three yeast strains, Saccharomyces cerevisiae I4, Clavispora lusitaniae 30 and Pichia kudriavzevii 11, isolated from traditional fermented dairy food in Xinjiang, China, on the ulcerative colitis symptoms of Balb/c mice treated by dextran sulfate sodium (DSS). Among which, S. cerevisiae I4 had good tolerance to simulated gastrointestinal juice and strong adhesion to HT−29 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…After yeast intervention, the relative abundance of Proteobacteria decreased, and that of Firmicutes increased to some degree ( Figure 7 ). Therefore, these yeasts reduced the microbiota structure imbalance, which is consistent with the results of a previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After yeast intervention, the relative abundance of Proteobacteria decreased, and that of Firmicutes increased to some degree ( Figure 7 ). Therefore, these yeasts reduced the microbiota structure imbalance, which is consistent with the results of a previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…S. boulardii CNCMI-745 and S. cerevisiae QHNLD8L1 significantly increased the relative expression levels of Claudin-1 and Occludin ( Figure 1 ). Similar to our results, S. cerevisiae I4 significantly upregulated these two genes in HT-29 cell monolayers [ 30 ]. Mu et al showed that yeast metabolites promoted RAW264.7 macrophage proliferation and reduced NO production [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…F. nucleatum could upregulate the canonical NF-κB pathway and increase the expression of proinflammatory cytokines, such as IL-6, IL-17F, TNF-α, IL-12, IL-21, and IL-22, all of which could promote triggering the colonic inflammation and carcinogenesis. , A decrease in the Bcl-2/Bax ratio can lead to an exacerbate disturbance in intestinal homeostasis and apoptosis. In this study, the expression of Bcl-2 was remarkably decreased (Figure A,F,H), and the Bax was increased after treatment with Fn and DSS at RNA and protein levels (Figure B,G,H).…”
Section: Resultsmentioning
confidence: 99%
“…cerevisiae in the colonic fungal flora of patients with colorectal cancer and IBD was lower than that of healthy subjects. , Other studies showed that supplementation with S. cerevisiae could alleviate DSS-induced colitis mice by downregulating the expression of proinflammatory cytokine (TNF-α), myeloperoxidase, and eosinophil peroxidase activities, regulating gut microbiota, and enhancing the intestinal barrier. , However, few studies have systematically investigated the mechanism by which S. cerevisiae intervenes in Fn-involved IBD by improving oxidative stress and regulating the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%